Role of esmolol in non-healing chronic wounds - Balar, Tasvir; Mago, Vishal; Reddy, Sushma; Arora, Adit; Kesharwani, Prakher; Kakani, Akshat; Saini, Rajnish (International Surgery Journal, 2026)
Background: Diabetic foot ulcers (DFUs) exhibit delayed healing due to persistent inflammation, oxidative stress, microvascular dysfunction, and impaired cellular responses. Topical esmolol hydrochloride has demonstrated wound‑healing potential through inhibition of aldose reductase, reduction of advanced glycation end products, and promotion of epithelial and endothelial migration. Methods: This observational cohort study included 30 patients with chronic, non‑infected foot or lower‑leg ulcers of more than three weeks’ duration, including diabetic (Wagner class 1A/1B) and non‑diabetic traumatic wounds. Patients received topical esmolol hydrochloride 14% once daily in addition to standard wound care. Wounds were assessed weekly for nine weeks using the Bates–Jensen wound assessment tool (BWAT). Complete healing was defined as full epithelialization without discharge. Results: Mean BWAT score improved from 28 at baseline to 3 at week 9, representing an 89.3% reduction. Complete healing within 9 weeks was achieved in 24 patients (80%). Healing was significantly higher in non‑anemic patients compared with anemic patients (p<0.05). Patients with normal serum albumin showed better outcomes, while glycemic control showed a positive but non‑significant association. Conclusions: Topical esmolol hydrochloride appears to be a safe and effective adjunct to standard wound care for diabetic and traumatic foot ulcers. Correction of systemic factors such as anemia and malnutrition further enhances outcomes. Larger randomized studies are required to confirm efficacy.